The Effect Of Socialization Group Activity Therapy Through Storytelling Cards On Improving Social Interaction Of Elderly People With Loneliness - Sabilah, Adinda Mutiara Ayu; Widagdo, Wahyu; Nurhaeni, Heni (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Indonesia, the number of people aged >60 years is increasing, leading to a high level of elderly dependency due to physical, mental, and social decline. Lack of social interaction can affect the quality of life of the elderly, leaving them isolated and lonely. This changes their role in social interaction in the family and society. This study aims to see the effect of providing socialization group activity therapy through storytelling cards in improving the social interaction of the elderly with loneliness. This research is a quantitative quasi-experiment one-group pretest-posttest with the control group, purposive sampling technique, and dependent t-test statistical test with a research sample of 60 respondents, 30 respondents for the intervention group and 30 respondents for the control group. The inclusion criteria for this study were age> 60 years, independent and cooperative elderly, living in PSTW for 1 month or more, understanding Indonesian (able to communicate well), having good hearing and vision, not suffering from stroke/other chronic diseases, and willing to become research respondents by giving informed consent. The exclusion criteria were the elderly <65 years old, did not live in PSTW, did not understand Indonesian (inability to communicate well), had poor hearing and vision, the elderly were suffering from stroke and other chronic diseases, and refused to be research subjects/respondents. This study used a social interaction questionnaire and a loneliness scale version 3 questionnaire developed by Russell in 1996. Statistically, the average result is 1.83333 from 30 respondents, and the p-value is 0.001. There is an effect of providing socialization group activity therapy through storytelling cards on increasing the social interaction of the elderly with loneliness.